PERAN POLRI DALAM MENANGANI TINDAK KEKERASAN DALAM RUMAH TANGGA - Wahyu Aditya (RECHTSTAAT, 2014)
The objectives of research were to study and to understand the role of the Republic of Indonesia’s Police (POLRI) in dealing with domestic violence, and to study and to understand the constraints in dealing with domestic violence.The methods of collecting data used were interview and library study. In this study, the writer employed two approaches: juridical normative, the one based on legislation and juridical sociological, the one viewing the problem existing in the society from the prevailing legislation.The result of research showed that: The role of POLRI in dealing with domestic violence included a) preventively by holding general seminar, giving recommendation, and lecturing concerning domestic violence, b) repressively, by conducting enquiry and investigation, c) protecting the victim in collaboration with related institution, d) deciding the Article when the perpetrator of domestic violence proved guilty. Then, the constraints in dealing with domestic violence included: a) limited number of witness, b) the victim did not report directly the incidence befalling her, c) the family reluctantly reported the domestic violence because the perpetrator was their member of family, and d) the society’s uncaring to domestic violence leading them to reluctantly interfere with the problem the family was facing. Keywords: Women, Violence, Family